Untargeted metabolic profiling of dogs with a suspected toxic mitochondrial myopathy using liquid chromatography-mass spectrometry. (August 2019) - Hunt, H.; Fraser, K.; Cave, N.J.; Gartrell, B.D.; Petersen, J.; Roe, W.D.
Abstract: 'Go Slow myopathy' (GSM) is a suspected toxic myopathy in dogs that primarily occurs in the North Island of New Zealand, and affected dogs usually have a history of consuming meat, offal or bones from wild pigs (including previously frozen and/or cooked meat). Previous epidemiological and pathological studies on GSM have demonstrated that changes in mitochondrial structure and function are most likely caused by an environmental toxin that dogs are exposed to through the ingestion of wild pig. The disease has clinical, histological and biochemical similarities to poisoning in people and animals from the plant Ageratina altissima (white snakeroot). Aqueous and lipid extracts were prepared from liver samples of 24 clinically normal dogs and 15 dogs with GSM for untargeted liquid chromatography-mass spectrometry. Group-wise comparisons of mass spectral data revealed 38 features that were significantly different (FDR<0.05) between normal dogs and those with GSM in aqueous extracts, and 316 significantly different features in lipid extracts. No definitive cause of the myopathy was identified, but alkaloids derived from several plant species were among the possible identities of features that were more abundant in liver samples from affected dogs compared to normal dogs. Mass spectral data also revealed that dogs with GSM have reduced hepatic phospholipid and sphingolipid concentrations relative to normal dogs. In addition, affected dogs had changes in the abundance of kynurenic acid, various dicarboxylic acids and N-acetylated branch chain amino acids, suggestive of mitochondrial dysfunction. Highlights: 'Go Slow' myopathy (GSM) of dogs in New Zealand has been associated with the ingestion of wild pig. The cause of GSM is unknown, although studies have demonstrated changes to the structure of mitochondria in affected dogs. Aqueous and lipid extracts of liver from 24 normal dogs and 15 dogs with the myopathy were analysed by LC-MS. No cause was identified, but several mass spectral features in GSM dogs could be consistent with plant-derived alkaloids. The disease is associated with changes in the abundance of phospholipids, kynurenic acid and N-acetylated amino acids.